Continuation theory for general contractions in gauge spaces - Radu Precup; Adela Chiş (Fixed Point Theory and Applications, 2004)
A continuation principle of Leray-Schauder type is presented for contractions with respect to a gauge structure depending on the homotopy parameter. The result involves the most general notion of a contractive map on a gauge space and in particular yields homotopy invariance results for several types of generalized contractions.